A comparative analysis of the relationship between flood experience and private flood mitigation behaviour in the regions of England. Issue 2 (6th February 2021) - Barendrecht, Marlies H.; McCarthy, Simon; Viglione, Alberto
Abstract: There has been a move towards a more integrated approach to flood risk management, which includes a stronger focus on property level measures. However, in England the uptake of these measures remains low. Flood experience has been found to influence preparedness (i.e., the uptake of measures), but even experience does not always result in an increase in preparedness. We investigate the variations in the relationship between experience and preparedness for the regions of England as defined by the Environment Agency. Analysis of survey data collected by the Environment Agency among the at risk population between 1997 and 2004 was undertaken to determine the differences between the seven regions. We find that in the South West, Southern and Anglian regions increases in preparedness with increasing experience are higher compared to other regions. In the Thames, Midlands and North West regions the preparedness increases less with increasing experience. We explore the influence of other factors influencing flood mitigation behaviour that have been previously found in the literature and find that the differences between regions are correlated with the severity of experienced flooding and whether English is the first language of the respondents.